Faktor-Faktor Pengembangan Kapasitas Dalam Pengelolaan Keuangan Daerah: Studi Kasus Unit Pelaksana Teknis Laboratorium Pengelolaan Keuangan Daerah Jawa Timur - Basnawi, Choiriyah (Journal of Governance and Administrative Reform, 2021)
This study aims to examine the factors that influence the development of human resource capacity in regional financial management through the Clinic Center by the Technical Implementation Unit of the East Java Regional Financial Management Laboratory. This research is motivated by the many problems that arise in regional financial management due to the low capacity of human resources in financial management. To overcome these problems, the East Java Provincial Government through BPKAD created an Innovation Regional Financial Management Laboratory which was later shortened to "Ini Lo Pakde" which became the first institution in Indonesia engaged in Capacity Building for regional financial management.Penelitian ini bertujuan meneliti faktor-faktor yang memengaruhi pengembangan kapasitas sumber daya manusia dalam pengelolaan keuangan daerah melalui Clinic Center oleh Unit Pelaksana Teknis Laboratorium Pengelolaan Keuangan Daerah Jatim. Penelitian ini dilatarbelakangi oleh masih banyaknya permasalahan-permasalahan yang muncul dalam pengelolaan keuangan daerah akibat rendahnya kapasitas sumber daya manusia dalam pengelolaan keuangan. Untuk mengatasi permasalahan tersebut, Pemerintah Provinsi Jatim melalui BPKAD membuat suatu Inovasi Laboratorium Pengelolaan Keuangan Daerah yang kemudian disingkat menjadi "Ini Lo Pakde” yang menjadi lembaga pertama di Indonesia yang bergerak dibidang Capacity Building pengelolaan keuangan daerah.